Application of the Point System on Improving Student's Discipline - Nurizatiningsih, Nurizatiningsih (PPSDP International Journal of Education, 2023)
This study tries to paint a picture of how the point system is used and how it affects student behavior. The methods used to acquire data include documentation, observations, and interviews. Data reduction, data exposure, and conclusions are all used in data analysis approaches. utilizing triangulation methods to validate data. The outcomes demonstrated that the point system’s deployment was done in order to enforce student discipline and make it easier to handle student infractions. Subject specialists, homeroom instructors, and picket teachers all apply the point system. The point system is created in the form of a pocket book that contains school regulations and the quantity of points that will be taken away if you break them. This book is referred to as a point book. Pupils start out with 200 points; if they break any school regulations, points will be taken away based on the infraction and added if they succeed. The point system’s adoption is hindered by certain teachers’ failure to administer it in compliance with the established standards, whereas it is supported by schools’ effective coordination in monitoring student disciplinary infractions.